1987
DOI: 10.3168/jds.s0022-0302(87)80184-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Protein on Reproductive Performance of Dairy Cows

Abstract: From 10 +/- 3.5 d after parturition to 149 +/- 3.5 d of lactation, 146 cows (109 Holstein and 37 Ayrshires) were fed either a 15 or 20% crude protein diet of 45% sorghum silage and 55% concentrate. Milk production was enhanced by the 20% protein diet, but percentage of milk fat and protein were unchanged. Average daily intake of DM was unaffected by diet. Actual decreases in body weight and condition were small, although cows on 15% protein lost more condition. Concentration of plasma urea nitrogen increased r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
9

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 17 publications
3
15
0
9
Order By: Relevance
“…Mean and median values were similar for all variables in this data set. A significant curvilinear relationship (R 2 = 0.19) was found between milk yield and the concentration of CP All data were taken or calculated from experiments reported in 112 independent studies (Barney et al, 1981;Mielke and Schingoethe, 1981;van Dijk et al, 1983;Henderson et al, 1985;Polan et al, 1985Polan et al, , 1997Van Horn et al, 1985;Broderick, 1986Broderick, , 1992Broderick, , 2003Lundquist et al, 1986;Annexstad et al, 1987;Garnsworthy and Jones, 1987;Howard et al, 1987;Jaquette et al, 1987;Kaim et al, 1987;Bowman et al, 1988;Hadsell and Sommerfeldt, 1988;Jones and Garnsworthy, 1988;Léonard and Block, 1988;Manson and Leaver, 1988;Robinson and Kennelly, 1988;Schingoethe et al, 1988;Sloan and Rowlinson, 1988;Voss et al, 1988;Bruckental et al, 1989Bruckental et al, , 2000De Gracia et al, 1989;Garnsworthy, 1989;Herrera-Saldana and Huber, 1989;Higginbotham et al, 1989;Mä ntysaari et al, 1989;Blauwiekel et al, 1990;Broderick et al, 1990Broderick et al, , 1993Canfield et al, 1990;Casper et al, 1990Casper et al, , 1999…”
Section: Performance Of Lactating Dairy Cowsmentioning
confidence: 99%
“…Mean and median values were similar for all variables in this data set. A significant curvilinear relationship (R 2 = 0.19) was found between milk yield and the concentration of CP All data were taken or calculated from experiments reported in 112 independent studies (Barney et al, 1981;Mielke and Schingoethe, 1981;van Dijk et al, 1983;Henderson et al, 1985;Polan et al, 1985Polan et al, , 1997Van Horn et al, 1985;Broderick, 1986Broderick, , 1992Broderick, , 2003Lundquist et al, 1986;Annexstad et al, 1987;Garnsworthy and Jones, 1987;Howard et al, 1987;Jaquette et al, 1987;Kaim et al, 1987;Bowman et al, 1988;Hadsell and Sommerfeldt, 1988;Jones and Garnsworthy, 1988;Léonard and Block, 1988;Manson and Leaver, 1988;Robinson and Kennelly, 1988;Schingoethe et al, 1988;Sloan and Rowlinson, 1988;Voss et al, 1988;Bruckental et al, 1989Bruckental et al, , 2000De Gracia et al, 1989;Garnsworthy, 1989;Herrera-Saldana and Huber, 1989;Higginbotham et al, 1989;Mä ntysaari et al, 1989;Blauwiekel et al, 1990;Broderick et al, 1990Broderick et al, , 1993Canfield et al, 1990;Casper et al, 1990Casper et al, , 1999…”
Section: Performance Of Lactating Dairy Cowsmentioning
confidence: 99%
“…Overfeeding proteins has been associated with a decline in fertility in most [6][7][8][9], but not all [10] studies. Jordan et al [11] found an increase in urea-nitrogen (N) concentration in the uterine secretions and plasma of cows fed 23% crude protein (CP).…”
Section: Introductionmentioning
confidence: 99%
“…Corroborando este argumento, Howard et al (1987) demonstraram que o livre acesso a uma dieta completamente misturada é um dos fatores responsáveis pela ausência de efeitos deletérios do excesso de proteína sobre a reprodução, como foi o caso do fornecimento da dieta no presente experimento.…”
Section: Experimento I: Uréia Na Alimentação De Doadoras De Embriõesunclassified
“…A forma da suplementação do nitrogênio não protéico e ou da proteína verdadeira, bem como a Tabela 7 -Análise bromatológica da pastagem das receptoras de embriões relação energia:proteína do suplemento e dieta total, deve ser aspecto fundamental para que não haja transtornos reprodutivos também para as vacas recptoras mantidas em pasto, conforme considerações importantes apontadas neste sentido por Erb et al (1976) e Howard et al (1987). Todas as receptoras que participaram do experimento e não confirmaram prenhez foram colocadas em estação de monta de novembro de 1999 a março de 2000.…”
Section: Experimento Ii: Uréia Na Alimentação De Receptoras De Embriõesunclassified